2005
DOI: 10.1007/s00701-005-0673-5
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive antibodies against neurons and basal lamina found in serum following experimental brain contusion in rats

Abstract: Experimental brain trauma and to some degree even sham surgery lead to an individually variable pattern of specific anti-brain reactive B-cells, while a T-cell response did not seem to be a consequence of moderate experimental contusion. The mere presence of anti brain-antibodies may be epiphenomenal, but could also be pathogenic for delayed degeneration. It is reasonable to regard the presence of an actual anti-brain reactivity as a potential threat to brain tissue integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Furthermore, autoreactive antibodies against neurons and basal lamina have been found in serum following experimental TBI in rats. The authors concluded that the presence of autoreactive antibodies against neurons and basal lamina after TBI could play a pathogenic role in the delayed neuron degeneration (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, autoreactive antibodies against neurons and basal lamina have been found in serum following experimental TBI in rats. The authors concluded that the presence of autoreactive antibodies against neurons and basal lamina after TBI could play a pathogenic role in the delayed neuron degeneration (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these mechanisms have been proven, and the mechanism of sports-related head trauma-induced pituitary dysfunction is still unclear. A possible role of autoimmunity has been suggested by studies conducted in animals, which demonstrated naturally occurring IgG autoantibodies against dying neurons in the injured brain of adult rats following a cortical lesion (13) and autoreactive antibodies against neurons and basal lamina in the serum of rats submitted to experimental TBI (14). Supporting these experimental findings, a significant association between antipituitary antibody (APA) positivity and hypopituitarism 3 years after TBI has been clearly demonstrated in a very recent clinical study (15).…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, autoreactive antibodies against neurons and basal lamina have been found in serum following experimental TBI in rats. The authors concluded that the presence of autoreactive antibodies against neurons and basal lamina after TBI could play a pathogenic role in the delayed neuron degeneration (8). Even if studies in humans investigating the occurrence of APA in patients with TBI are lacking in the literature, these antibodies have been detected in patients with selective idiopathic hypopituitarism and in adults with autoimmune endocrine diseases (9,11,13).…”
Section: Discussionmentioning
confidence: 99%
“…However, the dynamic changes in pituitary function suggest that head trauma may trigger an ongoing process such as autoimmunity (4). A possible role of autoimmunity could be suggested by studies in animals that demonstrated naturally occurring IgG autoantibodies against dying neurons in the injured brain of adult rats following a cortical lesion (7) and autoreactive antibodies against neurons and basal lamina in the serum of rats submitted to experimental TBI (8). Although the antibodies against neurons have been demonstrated in injured animal studies, investigations regarding the occurrence of antipituitary antibodies (APAs) in patients with TBI are lacking in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…16,46 Also, animal studies have shown a possible role of autoimmunity involving the hypothalamic-pituitary region and triggered by head trauma. 54,59 In a preliminary study, in 2008, Tanriverdi et al 61 investigated the presence of APAs in 29 patients with TBI 3 years after head trauma, and in 60 age-and sex-matched normal controls. The APAs were detected in 44.8% of TBI patients but in none of the controls.…”
Section: Antibodies Theorymentioning
confidence: 99%